Research progress on risk factors of aspiration pneumonia in patients with ischemic stroke (缺血性脑卒中患者吸入性肺炎危险因素研究进展) - GUO Qingyuan (郭清源); HE Yixian (和意娴); YANG Muwei (杨慕维); CAI Enli (蔡恩丽) (Journal of International Translational Medicine Limited, 2021)
Aspiration pneumonia is one of the common complications of patients with ischemic stroke. Understanding the related risk factors of it will help to identify high-risk patients early, and preventive measures are taken early after the occurrence of ischemic stroke to reduce the incidence of aspiration pneumonia. This article reviews the related risk factors of aspiration pneumonia in patients with ischemic stroke in order to provide ideas for disease prevention. (吸入性肺炎是缺血性脑卒中常见并发症之一, 了解其相关危险因素, 有助于医护人员早期识别高危患者, 积极采取有效预防措施, 从而降低缺血性脑卒中患者吸入性肺炎的发生风险。本文对缺血性脑卒中患者吸入性肺炎相关危险因素的研究进行综述, 旨在为本病的预防提供一定思路。)